Introducing Estrogen Metabolism as the Main Target of Wedelia chinensis in Prostate Cancer Cells - Vahid Mansouri; Mahmood Khodadoost*; Reza Mahmoud Robati; Zahra Razzaghi; Mitra Rezaei (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Investigations indicate that Wedelia chinensis extract increases efficacy of prostate cancer treatment. In the present study, the differentially expressed genes (DEGs) of prostate cancer cell line 22RV1 in the presence of W. chinensis extract derived from Gene Expression Omnibus (GEO) were evaluated by gene ontology and pathway analysis. Methods: Gene expression profiles of GSE100224 were analyzed by GEO2R. The significant DEGs were assessed via action map analysis. The related biological terms were identified for the significant DEGS. The highlighted dysregulated genes and pathways were discussed. Results: Seventy significant DEGs including 49 up-regulated genes and 21 down-regulated ones were assessed by inhibition, activation, expression, and binding actions. Cytochrome P450 and PTGS2 were highlighted as the crucial DEGs. Estrogen metabolism was pointed as the main targeted pathway.  Conclusion: Findings indicated that "estrogen metabolism" and UGT1A1, MAOA, PTSG2, and cytochrome P450 in the 22RV1 cells were the main targeted pathway and genes by W. chinensis .